2018
DOI: 10.1016/j.seizure.2018.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular myocardial deformation abnormalities in seizure-free children with epilepsy

Abstract: In seizure-free patients, cardiac systolic and diastolic functions were impaired when compared to healthy children. There was no difference in the patient group to explain the decline in cardiac functions and there may be unknown different factors besides the known risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…These studies showed a reduction in tissue Doppler E’ velocity consistent with our results. More significantly, our results are consistent with the results of the only other comparable study of advanced echocardiography and deformation in pediatric epilepsy patients 16 . These include normal EF and SF, impaired measures of systolic deformation, and impaired diastolic parameters as measured by mitral inflow and tissue Doppler velocities.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These studies showed a reduction in tissue Doppler E’ velocity consistent with our results. More significantly, our results are consistent with the results of the only other comparable study of advanced echocardiography and deformation in pediatric epilepsy patients 16 . These include normal EF and SF, impaired measures of systolic deformation, and impaired diastolic parameters as measured by mitral inflow and tissue Doppler velocities.…”
Section: Discussionsupporting
confidence: 91%
“…More significantly, our results are consistent with the results of the only other comparable study of advanced echocardiography and deformation in pediatric epilepsy patients. 16 These include normal EF and SF, impaired measures of systolic deformation, and impaired diastolic parameters as measured by mitral inflow and tissue Doppler velocities. Notably, the details of our subjects' epilepsy histories were not correlated with echocardiographic data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 19 , 20 Concerning mechanical dysfunction, recent studies demonstrated a reduced systolic and diastolic function in individuals with epilepsy, without evidence of a correlation between the echocardiographic findings and the severity of epilepsy. 21 , 22 Cardiac fibrosis and vascular dysfunction contribute to altering cardiac conduction and repolarization, thus generating a substrate for the development of arrhythmias. 23 Finally, as a result of the structural, functional, and electrical anomalies, a higher incidence of myocardial infarction (4.83‐fold increase) in epileptic individuals compared to the general population has been demonstrated.…”
Section: Epilepsy and Cardiac Comorbiditiesmentioning
confidence: 99%